GEOHYDRAULIC STUDY OF AQUIFER CHARACTERISTICS IN PARTS OF ENUGU NORTH LOCAL GOVERNMENT AREA OF ENUGU STATE USING ELECTRICAL RESISTIVITY SOUNDINGS - Oguama, Bethrand E.; Ibuot, Johnson Cletus; Obiora, Daniel N. (International Journal of Advances in Applied Sciences, 2020)
Geophysical survey employing Vertical Electrical Sounding (VES) was achieved in Enugu State College of Education (Technical). Schlumberger electrode configuration was used in acquiring the data which was interpreted using the WinrResist software. Four to five geoelectric layers were delineated from the interpreted results. The hydraulic parameters (hydraulic conductivity, porosity, formation factor, tortuosity and transmissivity) were estimated from the values of resistivity and thickness which are primary geoelectric parameters. The result shows the hydraulic conductivity varying from 2.71 to 70.45m/day, transmissivity: 49.2288 to1127.944 , porosity: 33.71 to 49.44%, formation factor: 0.0014 to 0.0026 and tortuosity: 0.2667 to 0.2935. The zones with high and low values of these parameters were delineated. The potentiality of the aquifer units show moderate to high, a reflection of the heterogeneity of the subsurface which is affected by the composition and geometry of the formation. The result from this study provides some important conclusions for future groundwater exploration and management.